Pengaruh Supervisi Kepala Sekolah Terhadap Pemahaman dan Penerapan Kurikulum Merdeka Belajar - Suryana; Hamengkubuwono; Fathurahman, Irwan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
SMA Negeri 1 Rejang Lebong is currently experiencing a significant educational transformation with the introduction of the Independent Learning Curriculum. Educational supervision at SMA Negeri 1 Rejang Lebong is a key instrument in ensuring teacher understanding and conformity of teaching methods with the Independent Learning Curriculum. The author uses a quantitative research approach, a type of research that collects data through questions in the form of questionnaires with a sample of 65 teachers at SMA Negeri 1 Rejang Lebong. The data analysis technique used can determine the measurement scale of each variable, so that hypothesis testing can be carried out appropriately. The aim of this research is to find out whether there is a significant influence between the principal's supervision on the understanding and implementation of the independent learning curriculum at SMA Negeri 1 Rejang Lebong. The conclusions obtained are (1) Principal supervision influences the understanding of the independent learning curriculum at SMA Negeri 1 Rejang Lebong, this can be seen from the significance of principal supervision of 0.917, which means it is greater than the significance level used, namely 0.05; (2) The principal's supervision influences the implementation of the independent learning curriculum at SMA Negeri 1 Rejang Lebong. This can be seen from the significance of the principal's supervision of 0.829, which means it is greater than the significance level used, namely 0.05. It can also be seen from the coefficient of determination of principal supervision of 0.687, that Ha is accepted and H0 is rejected; (3) There is an influence between the principal's supervision on the understanding and application of the independent learning curriculum at SMAN 1 Rejang Lebong, the principal's supervision has an effect of 84.1% on the teacher's understanding of the independent learning curriculum and the teacher's application of the independent learning curriculum by 68.7 %.